A Type III Monteggia Injury with Ipsilateral Fracture of the Distal Radius and Ulna in a Child: Case Report Followed for 21 Years. (21st June 2018) - Inoue, Takeshi; Kubota, Makoto; Marumo, Keishi
Abstract : Bado type III Monteggia injuries complicated by ipsilateral forearm fractures are extremely rare. We report a case of a 6-year-old boy who sustained such an injury after falling from the top of a 3 m climbing pole. He was diagnosed with a Bado type III Monteggia fracture and forearm fractures. Manual reduction was attempted on the day of injury. However, because it was difficult to maintain the reduction of the radial head, open and percutaneous procedures were performed to reduce and fixate the fractures with Kirschner wires. The postoperative course was favorable. Twenty-one years later, the patient, now 27 years old, had no decreased range of joint motion or problems with activities of daily living. The fracture morphology observed in this case is rare, and this is the only case for which long-term follow-up has been carried out to adulthood.